2010
DOI: 10.1007/s11426-010-0087-y
|View full text |Cite
|
Sign up to set email alerts
|

Ni supported on activated carbon as catalyst for flue gas desulfurization

Abstract: A series of Ni supported on activated carbon are prepared by excessive impregnation and the desulfurization activity is investigated. It has been shown that the activated carbon-supported Ni is an efficient solid catalyst for flue gas desulfurization. The activated carbon treated by HNO 3 exhibits high desulfurization activity, and different amounts of loaded-Ni on activated carbon significantly influence the desulfurization activity. The catalysts are studied by X-ray diffraction (XRD) and X-ray photoelectron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…3b, c, d. The high resolution of C1s spectrum could be fitted into three individual peaks located at around 284, 285, and 286 eV, corresponding to the C-C, C-N, and C-O binding, respectively [23]. The contents of different functional groups from XPS spectrum after peak fitting are listed in Table 2.…”
Section: Surface Chemistry Of Cigarette Butt-derived Activated Carbonsmentioning
confidence: 99%
“…3b, c, d. The high resolution of C1s spectrum could be fitted into three individual peaks located at around 284, 285, and 286 eV, corresponding to the C-C, C-N, and C-O binding, respectively [23]. The contents of different functional groups from XPS spectrum after peak fitting are listed in Table 2.…”
Section: Surface Chemistry Of Cigarette Butt-derived Activated Carbonsmentioning
confidence: 99%
“…The active sites activated by NO molecules may be related to the Cu species, 20 and the active sites of CuO show easy redox effects with reactants. 21,22 The good redox performance, sufficient surface oxygen vacancies and high oxygen storage/release capabilities of NiO have attracted special attention, 23,24 and it is also widely used in CO-SCR denitration catalysts. In previous works, 25,26 it was found that in the process of copper-nickel coordinated loading, in addition to affecting the selectivity and denitrication activity of NO gas, Cu can prevent the formation of carbon deposits and the sintering of Ni nanoparticles and reduce the reduction temperature of NiO.…”
Section: Introductionmentioning
confidence: 99%
“…Spassova et al have performed research on the denitration performance of copper-based catalyst CO-SCR with Ce and Co as promoters and concluded that there was a catalytic synergy between the active component Cu and the promoter, which was beneficial to improving the denitration activity of the catalyst. Because NiO has good redox performance, sufficient surface oxygen vacancies (SOV), and high oxygen storage/release capabilities, it has attracted special attention, , and it is widely used in the CO + NO reaction. This occurs because oxygen (Oa), which is required for the denitration reaction, is generated in the Ni 3+ /Ni 2+ redox cycle .…”
Section: Introductionmentioning
confidence: 99%